High electro-mechanical coupling coefficient SAW device with ScAlN on diamond. (1st February 2023) - Hatashita, K.; Tsuchiya, T.; Okazaki, M.; Nakano, M.; Anggraini, S. A.; Hirata, K.; Ohmagari, S.; Uehara, M.; Yamada, H.; Akiyama, M.; Shikata, S.
Abstract: In this study, Sc concentration dependence of Sc x Al1− x N/AlN/poly-crystalline diamond/Si surface acoustic wave (SAW) characteristics at high Sc from 23.8% to 44.3% was investigated by fabricating one-port SAW resonator at high frequency. 3.8 GHz one-port resonator fabricated on Sc0.43 Al0.57 N showed an excellent performance of electro-mechanical coupling coefficient ( K 2 ) as high as 6.34% for 2nd mode Sezawa wave, which enables a wide bandwidth in high frequency applications. The temperature coefficient of frequency was approximately −40 to −50 ppm deg −1 for the device fabricated with Sc concentration of 42.9%. This is a smaller value compared to conventional high K 2 bulk materials such as LiNbO3 . As the result, a high K 2 6.34% material system at a higher Sc concentration of ScAlN/AlN/PCD was found to be possible at a high phase velocity of 7000 m s −1 . Combined with the extremely high-power durability of diamond based device, high-power durable wideband SAW device at high frequency can be expected.